Chapter Insights from the Fields: the Role of Reflection in 'Learning How to Learn' - Salerni, Anna (Studies on Adult Learning and Education, 2018)
In experiential learning, on-field experience needs to be processed consciously in order for learning to take place. Reflection plays a crucial role by providing a bridge between practical experience and conceptualization. Despite being a protected environment, university traineeship is a form of experiential learning that offers students a chance to learn from the fields and reflect on a possible future profession. In this paper we present and discuss a research project whose goal is the development of a methodology to educate trainees' reflective thinking and writing